Constitutional Issue of the Executional Power of Fiduciary Certificates as Equal to Court Decision - Elisabeth Nurhaini Butarbutar (Jurnal Konstitusi, 2022)
The enactment of the Fiduciary Guarantee Law is expected to be able to answer problems in the financing business, but it causes a loss of constitutional rights because it equalizes the executorial power of a judge's decision legally binding with fiduciary certificates. The analysis was carried out by Constitutional Court Decision Number 18/ PUU-XVII/2019; the was carried out by document study and analyzed prescriptively and descriptively. The results showed that the normative basis of the executive power on the fiduciary certificate was born from an agreement registered. So that it can be used as perfect evidence to prove the debtor in breach of contract, and the judge's legal consideration to declare the inconsistent provisions tested are based on not the existence of legal certainty in determining the time of breach of contract (default) and the mechanism for the execution of the Fiduciary Certificate